Tinjauan Kriminologi Tentang Bentuk dan Upaya Penanggulangan Kekerasan terhadap Anak di Kota Kupang - Rosa Virginia Wona; Rudepel Petrus Leo; Heryanto Amalo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The purpose of this research is to analyze the criminological review of the forms and efforts to overcome violence against children in Kupang City. This research is an empirical juridical research that uses data collection techniques through interviews, documentation studies to obtain primary and secondary data on Criminology Review of Forms and Efforts to Overcome Violence Against Children in Kupang City, the data is descriptively qualitative. The results of this study indicate that the forms of violence that occur in Kupang City, physical violence, namely all acts of torture, beatings and abuse of children with or without the use of objects that cause physical injury or death to children, emotional / psychological violence, namely situations of feeling unsafe and comfortable experienced by children. Sexual violence is when children are sexually abused/treated and also involved or take part in or see activities of a sexual nature with the aim of pornography, body movements, movies or something that aims to exploit sex where someone satisfies their sexual appetite for others. Economic abuse is the abuse of a child's labor for work and other activities for the benefit of their parents or others. Child neglect/exploitation is the attitude and behavior of parents who do not provide proper attention to the child's growth and development process. Efforts made against cases of child abuse are preemptive efforts, initial efforts made by the police to prevent the occurrence of a criminal act, preventive efforts, preventive measures taken by the authorities before the occurrence of a criminal act, repressive efforts, countermeasures made by the authorities after a criminal act has occurred.